Validity and reliability of physical employment standards - Milligan, Gemma S.; Reilly, Tara J.; Zumbo, Bruno D.; Tipton, Michael J. (Applied physiology, nutrition, and metabolism, 2016)
In this paper the role of validity and reliability in the development of physical employment standards (PESs) and the consideration of these factors in determining the final pass/fail criteria for a PES and ultimately the legal defensibility of a PES is examined. Particular attention is paid to the use of subject-matter experts, the levels of evidence used in the establishment of the minimum acceptable pace/intensity for the completion of critical tasks, and the considerations needed in physical test selection.